Алексея Петрова Полонез по-русски , или Заграница.рl.ги. - сюжет русско-польской взаимности - Dmitrowski, Aleksiej (Acta Polono-Ruthenica, 2008)
The documentary novel as a discourse of the Russian-Polish mutual relations in dramatic collisions and commonness. The architectonics of the novel in the ratio of the fabulous mutual visits of the Russian authors and his Polish friends and the structure of the deep historic insight. The compositional structure is in the exchange of Polish and Russian episodes. The friendship of the Russian spouses as a pattern of obligatory relations on the confidential (private), interstate and national level.